Implementasi Program Pemberian Makanan Tambahan (PMT) Berbasis Pangan Lokal dalam Upaya Penanggulangan Stunting di Kabupaten Donggala - Oktavia, Sriyani; Sudirman, Sudirman; Budiman, Budiman (Syntax Corporation, 2025)
Stunting remains a major public health issue in Indonesia, particularly in Donggala Regency, where the prevalence rate remains high. The Local-Based Supplementary Feeding (PMT) program is one of the government’s specific interventions aimed at reducing stunting through the utilization of local nutritious foods. This study aimed to analyze the implementation of the PMT program in Donggala Regency using Edward III’s policy implementation model, which consists of four variables: communication, resources, disposition, and bureaucratic structure. The research employed a mixed-method approach with an explanatory sequential design involving 99 respondents and 12 qualitative informants. Quantitative data were analyzed using chi-square and multiple logistic regression tests. The results showed that all four variables—communication (p=0.000), resources (p=0.000), disposition (p=0.000), and bureaucratic structure (p=0.000)—had a significant influence on program implementation. The logistic regression analysis indicated that disposition was the most influential variable (p=0.001; Exp(B)=7.215), reflecting the strong impact of the implementers’ attitudes and commitment on the program’s success. Qualitative findings supported this, showing that effective communication, sufficient resources, and efficient coordination strengthened implementation outcomes. In conclusion, improving implementers’ commitment, inter-sectoral coordination, and community participation is crucial for enhancing the sustainability and effectiveness of the local-based PMT program in reducing stunting in Donggala Regency.